The family creative workshop : rosemaling rubbings rya and flossa sail making and repair samplers sandak making sand casting sand castles sand painting and layering sashimi and sushi scrimshaw - Bragdon, Allen Davenport (Plenary Publications International, 1976)
128 p. : il.; 27 cm.